دراسة مقارنة لمرضى قصور الدرق في ثلاث مدن سورية - فاضل, هيام (Latakia University Journal -Biological Sciences Series, 2019)
تهدف هذه الدراسة إلى مقارنة قصور الدرق عند مرضى من مدن سورية مختلفة الارتفاع عن سطح البحر ومعرفة تأثير التغذية على نشاط الغدة الدرقية. شملت الدراسة 150 مريضاً بقصور الدرق، وذلك بمعدل 50 مريضاً من كل مدينة (اللاذقية، إدلب (سراقب)، حلب)، إضافة إلى المجموعة الشاهدة والتي تضمنت 50 شخصاً سليماً. بيّنت النتائج أن انتشار مرض القصور الدرقي كان واضحاً في المدن الثلاث وذلك مقارنة بالشاهد. كما بيّنت النتائج أن ظهور مرض القصور الدرقي كان أكثر انتشاراً في مدينة حلب، وأقل انتشاراً في اللاذقية. ويعود السبب في ذلك لكون مدينة حلب أكثر ارتفاعاً عن سطح البحر، ويعتمد سكانها في تغذيتهم على نباتات الفصيلة الصليبية (كالملفوف والقرنبيط)، مقارنة مع سكان اللاذقية الأقرب إلى سطح البحر والأكثر تناولاً للمأكولات البحرية( الأسماك) الغنية باليود. This study aims to compare patients with Hypothyroidism in Syrian cities with different levels above the sea, and see the effect of nutrition on the activity of the thyroid gland. The study included 150 patients with hypothyroidism at the rate of 50 patients from each city LATAKIA, IDLEB (SARAKEB) , ALEPPO, in addition to the control group, which included 50 healthy persons. Results show that the spread Hypothyroidism was evident in the three cities, compared to the control. The results also show that the emergence of hypothyroidism was more prevalent in the city of ALEPPO, and less prevalent in LATAKIA . This is due to the fact that the city of ALEPPO is higher above sea level, and Nutrition of population depends on plants species of theCruciferaeas cabbage and cauliflower, compared with the population of people of LATAKIA, who are nearer to the sea and eat more seafood (fishes) rich in iodine.